The implementation of discovery learning to improve scientific literacy in biology learning of protists - Rosamsi, Saiman; Aryanti, Fitri (JPBIO (Jurnal Pendidikan Biologi), 2025)
This study highlights the importance of developing 21st-century competencies, particularly students’ abilities to explain scientific phenomena, design investigations, and interpret data and evidence. The topic of Protists was chosen due to its high diversity and complexity, which often makes it difficult for students to understand, requiring a learning strategy that emphasizes active exploration and concept discovery. The study aimed to examine the effect of the Discovery Learning model on students’ scientific literacy in biology. A quasi-experimental pretest–posttest control group design was employed with two purposively selected tenth-grade classes in a senior high school. The experimental class (n = 20) used the Discovery Learning model, while the control class (n = 20) received conventional instruction. A scientific literacy test based on PISA indicators was used as the instrument. Results showed the experimental class’s mean score increased from 36.33 to 83.33, with an N-Gain of 0.70 (high category). Normality (p > 0.05) and homogeneity (p > 0.05) assumptions were met, and One-Way ANOVA (p < 0.05) indicated a significant difference, suggesting that Discovery Learning effectively improves students’ scientific literacy through active exploration, data analysis, and concept discovery.